(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Consumer protection in consumer protection laws are all efforts that guarantee legal certainty to provide protection to consumers. Legal certainty in this case is that consumers have the right to obtain all information from goods sold both in terms of specifications and quality.In practice, there are still buying and selling transactions that are not in accordance with legal certainty. As in the village of Plangkapan, there are still buying and selling fake motorbikes that are not accompanied by official papers or documents. Here the object is not clear whether the motorbike was stolen or the papers were lost. The people who bought the motorbike did not see whether the motorbike was stolen or the documents were lost, but only saw its useful days for the benefit of its activities. This type of research is field research, with a socio-juridical approach and using observation methods, documentation interviews using purposive sampling techniques which are then analyzed using descriptive- qualitative methods. The problem is how to buy and sell bogus motorbikes in Plangkapan Village, Tambak District, Banyumas Regency and how to buy and sell fake motorbikes in Plangkapan Village from the Perspective of Law No. 8 of 1999 concerning Consumer Protection and Islamic Law. The results showed that in the practice of buying and selling motorbikes in the practice of buying and selling in the village of Plangkapan, the results showed that the motorbike was stolen, removed from the dealer and bought a used motorbike, then the motorbike was sold without official papers or documents. The buyer did not get clear information about the motorbike. But the buyer still agreed with the buying and selling system because motorcycle buyers only see in terms of benefits. In Islamic law buying and selling motorbikes from theft is a fasid law. However, if buying and selling fake motorbikes is not the result of theft, it is permissible. Whereas in the Consumer Protection Act, the sale and purchase of bodong motorbikes violates the provisions on consumer rights, the obligations of business actors and actions that are prohibited by business actors, as well as the lack of ownership protection for consumers